Ocena zmožnosti vožnje z vozičkom za otroke na testnem poligonu - Trontelj, Benjamin (Rehabilitacija (Ljubljana), 2020)
Introduction: The choice of the appropriate wheelchair category is influenced by the functional abilities of the child. Later, the child must also learn how to use his/her wheelchair. We wanted to find a suitable test or develop our own. Methods: In the Medline database, we searched for a test that could be used for children who are still learning to drive, regardless of diagnosis. Because we could not find any, we developed our own test, which comprises 31 items. In the preliminary testing phase, we included children who were referred to the rehabilitation program from June 2019 to January 2020. We also created a test polygon to assess wheelchair driving in a standardised way. Results: Testing with the first version was performed by one child, and with the second version by 13 children, mostly with cerebral palsy (mean age 9 years). Children achieved the highest average results in the basic driving skills domain with an active wheelchair and electric-powered wheelchair (80 % and 88 % of possible score, respectively). The lowest average result was achieved in the domain of physical control of the wheelchair (24 %). Conclusion: Children have different abilities to drive a wheelchair on the polygon. They mostly have problems with the physical control of the wheelchair and joining the traffic. Further research is needed for assessing psychometric properties of the test.
Keywords: Child; invalidski voziček; minimal clinically important difference; obvladovanje vozička; otrok; test; wheelchair; wheelchair mobility skills; Wheelchairs